2011
DOI: 10.1007/7854_2011_191
|View full text |Cite
|
Sign up to set email alerts
|

Behavioral and Pharmacogenetics of Aggressive Behavior

Abstract: Serotonin (5-HT) has long been considered as a key transmitter in the neurocircuitry controlling aggression. Impaired regulation of each subtype of 5-HT receptor, 5-HT transporter, synthetic and metabolic enzymes has been linked particularly to impulsive aggression. The current summary focuses mostly on recent findings from pharmacological and genetic studies. The pharmacological treatments and genetic manipulations or polymorphisms of a specific target (e.g., 5-HT1A receptor) can often result in inconsistent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
63
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(67 citation statements)
references
References 429 publications
(394 reference statements)
4
63
0
Order By: Relevance
“…Therefore, it can be assumed that the sensitivity of 5-HT 2A receptors to their ligands, and particularly to the antagonists, depends on different contribution of this receptor subtype to aggressive behaviors, and may explain dissimilar effects of ketanserin on immunity in aggressive rats and mice, observed in our experiments. It should also be considered that application of both agonists and antagonists of 5-HT 2A receptors in patients with various neuropsychiatric disorders and in several animal species is associated with the side effects of these compounds, such as the cognitive deficits, sedation or hypolocomotion [4] [5] [34], that, in turn, may differently affect immune reactivity in animals.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, it can be assumed that the sensitivity of 5-HT 2A receptors to their ligands, and particularly to the antagonists, depends on different contribution of this receptor subtype to aggressive behaviors, and may explain dissimilar effects of ketanserin on immunity in aggressive rats and mice, observed in our experiments. It should also be considered that application of both agonists and antagonists of 5-HT 2A receptors in patients with various neuropsychiatric disorders and in several animal species is associated with the side effects of these compounds, such as the cognitive deficits, sedation or hypolocomotion [4] [5] [34], that, in turn, may differently affect immune reactivity in animals.…”
Section: Discussionmentioning
confidence: 99%
“…Among several types of 5-HT receptors, 5-HT 2A receptors have long been implicated in the pathophysiology of aggressive behaviors [1]- [6]. Moreover, a number of atypical antipsychotic drugs and antidepressants, targeting 5-HT 2A receptors, have been successfully used in patients with various neuropsychiatric disorders [4], which are known to be associated with abnormal aggression and altered immune function [7]- [9]. A number of studies have also demonstrated that 5-HT receptor subtypes are involved in the 5-HTergic mechanisms of immunomodulation [10]- [18].…”
Section: Introductionmentioning
confidence: 99%
“…The highest, cortical control influencing maternal responses implies the involvement of the medial prefrontal cortex (mPFC) in maternal adaptations [6][7][8]. In addition, the mPFC is part of the limbic system and is associated with emotional changes, including anxiety, stress responses, and depression, as well as aggression [9][10][11][12][13][14][15]. Impaired maternal responsiveness in human mothers suffering from postpartum depression (PPD) has been shown to be associated with reduced activity in brain areas corresponding to the mPFC [16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…An implusive temperament is associated with clinical conditions, such as pathological gambling, eating disorders, and borderline personality disorder as well as being a risk factor for self-harm, suicide, and emotional liability [3,7]. Brain imaging and pharmacogenetic studies have demonstrated that serotonin dysfunction is associated with impulsive behaviors [8]. Aggression is not a personality trait like impulsivity, but it is the behavior of harm or injury to others [9].…”
Section: Introductionmentioning
confidence: 99%